2011
DOI: 10.1074/jbc.m110.216390
|View full text |Cite
|
Sign up to set email alerts
|

A Germ Cell-specific Gene, Prmt5, Works in Somatic Cell Reprogramming

Abstract: Germ cells possess the unique ability to acquire totipotency during development in vivo as well as give rise to pluripotent stem cells under the appropriate conditions in vitro. Recent studies in which somatic cells were experimentally converted into pluripotent stem cells revealed that genes expressed in primordial germ cells (PGCs), such as Oct3/4, Sox2, and Lin28, are involved in this reprogramming. These findings suggest that PGCs may be useful for identifying factors that successfully and efficiently repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 33 publications
3
69
0
Order By: Relevance
“…S1C; Supplemental Table S1). This stringently defined list concentrates factors that were previously identified as facilitators of reprogramming, such as Ezh2, Suz12, Wdr5, Sirt6, and Prmt5 (Ang et al 2011;Nagamatsu et al 2011;Onder et al 2012;Sharma et al 2013;Ding et al 2014), thus validating our screen. However, it also included many factors that have not been previously implicated in reprogramming.…”
Section: A Functional Rnai Screen For Epigenetic Regulators Of Reprogmentioning
confidence: 99%
“…S1C; Supplemental Table S1). This stringently defined list concentrates factors that were previously identified as facilitators of reprogramming, such as Ezh2, Suz12, Wdr5, Sirt6, and Prmt5 (Ang et al 2011;Nagamatsu et al 2011;Onder et al 2012;Sharma et al 2013;Ding et al 2014), thus validating our screen. However, it also included many factors that have not been previously implicated in reprogramming.…”
Section: A Functional Rnai Screen For Epigenetic Regulators Of Reprogmentioning
confidence: 99%
“…Interestingly, PRMT5S enhanced the differentiation of dendritic cells whereas PRMT5L showed an inhibitory effect in ectopic expression assays (M. Sohail, S. Kung, and J. Xie, unpublished data). The different effects on cellular processes along with spatially and temporally regulated alternative splicing of the two variants thus likely contribute to the diverse roles of PRMT5, including but not limited to the maintenance of stem cell pluripotency and promotion of cancer cell growth as well as cell differentiation (34,(41)(42)(43)(44)(45)(46)62). Understanding these effects could be facilitated by revealing the potentially different profiles of methylation targets and enzyme activities of the PRMT5 isoforms in subcellular locations and compartments in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It controls gene transcription/RNA processing (32,(38)(39)(40), maintains circadian rhythm and stem cell pluripotency or proliferation (34,(40)(41)(42)(43), accelerates cell cycle progression (44,45), and promotes tumorigenesis (37,46). However, the molecular basis of these diverse roles in cellular processes has not been fully understood.…”
mentioning
confidence: 99%
“…Although Blimp1 (Prdm1) is required for development of the posterior limb bud, the mutant phenotype is different from that of Prmt5 cKOs (Robertson et al, 2007), implying a different mechanism of regulation. In several stem cell populations, PRMT5 helps maintain pluripotency by inhibiting differentiation factors (Ancelin et al, 2006;Nagamatsu et al, 2011;Tee et al, 2010), suggesting that a similar mechanism could be regulating both stem cells and progenitor cells within the limb bud during development. Interestingly, an in vivo population of Grem1-expressing mesenchymal skeletal stem cells was recently identified that has the potential to give rise to bone and cartilage in postnatal animals (Worthley et al, 2015).…”
Section: Prmt5-mediated Mechanisms For Maintaining Progenitor Cellsmentioning
confidence: 99%